Thin description: ethnography and the African Hebrew Israelites of Jerusalem - Jackson, John L. (Harvard University Press, 2013)
African Hebrew Israelites of Jerusalem are often dismissed as a fringe cult, but John L. Jackson questions what "fringe" means when cultural practices of every stripe circulate freely on the Internet. He reveals how race, religion, and ethnographic representation must be understood anew in the 21st century lest we reenact past errors